CELL PRODUCTION SYSTEM IN PRODUCTION MANAGEMENT IN RECREATION FACILITIES - Kepoglu, Abdurrahman; Bayansalduz, Mehmet (Acta Scientiae et Intellectus, 2024)
Our study presents a holistic method prepared according to the principles of axiomatic design (AD) for designers who want to transform a functionally placed production system into a production system consisting of cells. This method, developed according to the axiom of independence, systematically provides all the steps in the cellular production system transformation process. It also includes the feedback system that enables the evaluation and development of the cellular production system according to the determined performance criteria. The method is specifically designed for a recreation business that produces a trekking product in an indoor/outdoor area. The developments obtained as a result of the application are also shown within the scope of the study.